2021
DOI: 10.29309/tpmj/2021.28.12.6164
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression among medical students: A Cross-Sectional Study.

Abstract: Objectives: To determine the prevalence of depression among medical students and its association with various sociodemographic characteristics. Study Design: Cross-Sectional Study. Setting: Nishtar Medical University, Multan. Period: August 2019 to September 2020. Material & Methods: A sample of 315 medical students were chosen by stratified random sampling technique. Patient Health Questionnaire 9 (PHQ-9) was used for screening and assessing the severity of depression. A special questionnaire was designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The prevalence of hypertension among young adults in this population is lower than in a study in Zimbabwe, i.e., 7.4%, based on survey conducted in Harare, Bulawayo, and Mashonaland East (Sabapathy et al, 2023). Similarly, a study conducted in Lahore, Pakistan showed that the prevalence of hypertension among young adults was 15.7% (Zaib Zahid et al, 2023). The study conducted in India has a higher prevalence of hypertension among young adults, i.e., 13.8%, based on The National Family Health Survey-4 data (Krishnamoorthy et al, 2023).…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence of hypertension among young adults in this population is lower than in a study in Zimbabwe, i.e., 7.4%, based on survey conducted in Harare, Bulawayo, and Mashonaland East (Sabapathy et al, 2023). Similarly, a study conducted in Lahore, Pakistan showed that the prevalence of hypertension among young adults was 15.7% (Zaib Zahid et al, 2023). The study conducted in India has a higher prevalence of hypertension among young adults, i.e., 13.8%, based on The National Family Health Survey-4 data (Krishnamoorthy et al, 2023).…”
Section: Discussionmentioning
confidence: 96%